Research on exploring college students’ online English learning performance through NetEase cloud classroom - Zhang, Qi; Masran, Md Nasir Bin; Hou, Yanghong (Frontiers in Education, 2025)
With the rapid development of information technology, online learning platforms have been widely used in higher education. However, the actual learning outcomes of students have yet to be verified. To this end, this study set three research objectives: (1) to explore the current status of college students’ English online learning engagement on the NetEase Cloud Classroom platform; (2) to analyze the differences in learning engagement under different demographic variables; and (3) to identify the main factors affecting college students’ English online learning engagement and propose improvement strategies. Based on the learning engagement theory, this study comprehensively examines the impact of learner individual factors, teacher factors, and online learning environmental factors on learning engagement. Based on the lit-erature review and existing scales, combined with the actual situation of English learning on the NetEase Cloud Classroom, a questionnaire was compiled and a questionnaire survey was conducted on college students from multiple universities in Shanghai. A total of 497 ques-tionnaires were collected in the initial test, verifying the reliability and validity of the scale; 884 valid questionnaires were collected in the formal survey, and descriptive statistics, correlation analysis, and multiple regression analysis were performed using SPSS 30 and AMOS 30.0. In order to ensure the reliability of the data, this study also selected 15 students for semi-structured interviews and referred to the learning data of the NetEase Cloud Classroom platform for multi-source verification. The results show that the overall level of English learning engagement of college students is good, but there is an imbalance in each dimension. Among them, cognitive engagement has the strong-est correlation with overall learning engagement. Self-efficacy, perceived teacher support and online learning platform usage experience have a significant positive impact on learning engagement, and the degree of influence is in the order of self-efficacy > perceived teacher support > online learning platform. So this paper proposes corresponding improvement strategies, including strengthening self-management ability, improving teachers’ guidance and support, building a learning community to pro-mote communication and interaction, and optimizing the overall design and assessment methods of the online learning platform, so as to further improve students’ learning outcomes.